Application of Factorial Design of Experiments for the Continuous Hydrogenation of Enriched Castor Oil Methyl Esters - Tulasi Sri Venkata Ramana Neeharika; Karna Narayana Prasanna Rani; Kasturi Venkata Sesha Adinarayana Rao; Thella Prathap Kumar; Rachapudi Badari Narayana Prasad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
Castor oil methyl esters contains nearly 90% ricinoleic acid (12-hydroxy-cis-9-octadecenoic acid). Hydrogen-ated castor oil methyl esters finds several applications in coating, lubricants formulations and pharmaceu-tical areas. The present study reports a fast, simple, efficient and continuous hydrogenation of enriched castor oil methyl ester (ECME) using 10% Pd/C catalyst at different pressures and temperatures. The range of process conditions for this study varied from 30-60 °C, 5-15 bar with constant flow rate of 15 ml/min. The products were analyzed for fatty acid composition and iodine value (IV). The optimized pa-rameters were found to be a temperature of 30 °C, pressure 5 bar, and flow rate of 15 ml/min where maxi-mum hydrogenation of 98.47 % was obtained and the product showed an iodine value of 3.19. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)